2015
DOI: 10.1177/0040517515596926
|View full text |Cite
|
Sign up to set email alerts
|

Total heat loss as a predictor of physiological response in wildland firefighter gear

Abstract: In most types of protective clothing heat strain is an important issue. The wildland firefighter clothing system in the USA has seen no major revision over the last decades. In this project the wildland firefighter clothing system was studied at the material and the systems level. On the sweating guarded hot plate and the sweating thermal manikin effects of different base layers (cotton and modacrylic) and meta-aramid outer layers of different fabric weights were evaluated. Then, a human subject trial was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The increase in T gi found in this study ( Figure 2 ) seems to indicate that the subjects reached a situation of uncompensable heat stress during the tests ( Den Hartog et al, 2016 ). It has been previously reported that a temperature above 38°C may be a limiting factor of performance during exercise in the heat ( González-Alonso et al, 1999 ).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The increase in T gi found in this study ( Figure 2 ) seems to indicate that the subjects reached a situation of uncompensable heat stress during the tests ( Den Hartog et al, 2016 ). It has been previously reported that a temperature above 38°C may be a limiting factor of performance during exercise in the heat ( González-Alonso et al, 1999 ).…”
Section: Discussionsupporting
confidence: 57%
“…In general, the PPC protective characteristics may interfere with thermoregulation, reducing or preventing the heat transfer and sweat evaporation ( Holmér, 2006 ; Cheung et al, 2010 ; Carballo-Leyenda et al, 2017 ). Therefore, the study of the wildland firefighters’ thermophysiological response to different PPC has acquired special relevance in recent years ( Den Hartog et al, 2016 ; Carballo-Leyenda et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations